VCO Enterprise / Ahmad Faisal Mohd...[et.al] - Mohd, Ahmad Faisal; Sazali, Nur Hasanah; Mohd Yasin, Muzainah; Zulkefly, Zuazlina; Abdullah, Nur Yasmin Zaini (Faculty of Plantation and Agrotechnology, 2015)
VCO Enterprise was incorporated in Jasin, Melaka. This company is incorporated for the purpose of enforce agriculture sector by using pure extraction of coconut oil from pandan variety. This is in compliance with the government vision in "Rancangan Malaysia Ke-9" (RMK-I0) stated where the government encourage the involvement of public sector in development of agriculture sector. This site of our project is stated on 3 acre land which already planted with coconut and located Simpang Kerayong, Jasin, near our office at Jasin town. The nature of our business are manufacturing and selling. As for beginning, we will only using the coconut from our farm as mentioned previously to ensure high quality materials for our products. We are ensuring that our products are highly effective and completely made from all natural ingredients extracted using high technology machineries.. We will target several areas in Melaka such as UiTM KJM, Politeknik Merlimau and few places in Semabok. Details information and certificates will be given along with the products to give brief information for the users about our products specials which are highly guaranteed by associate researchers. We're aiming for a better and conducive growth and return from what we will invest in the business.